The great leopard rescue : saving the Amur leopards - Markle, Sandra (Millbrook Press, 2017)
"Amur leopards are the rarest big cats in the world. But thanks to scientists' new, innovative efforts to study them and breed a reserve population, these majestic cats have a chance to come back."--